2021
DOI: 10.3390/ma14040776
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sn-3.0Ag-0.5Cu Composite Solder with Kaolin Geopolymer Ceramic Reinforcement on Microstructure and Mechanical Properties under Isothermal Ageing

Abstract: This paper elucidates the effect of isothermal ageing at temperature of 85 °C, 125 °C and 150 °C for 100, 500 and 1000 h on Sn-3.0Ag-0.5Cu (SAC305) lead-free solder with the addition of 1 wt% kaolin geopolymer ceramic (KGC) reinforcement particles. SAC305-KGC composite solders were fabricated through powder metallurgy using a hybrid microwave sintering method and reflowed on copper substrate printed circuit board with an organic solderability preservative surface finish. The results revealed that, the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Tang et al [29] reported that the grain size of Cu 6 Sn 5 IMC increased with increasing reflow time, but the addition of TiO 2 suppressed the growth of the IMC due to TiO 2 particles preventing the diffusion between Cu and Sn atoms. It was also reported that the solder properties improved due to the enhancement in the growth of the interfacial IMC layer [20,24,26,30]. Therefore, it can be surmised that the growth of the IMC layers during multiple reflow soldering needs to be controlled or limited as it improves solder properties and ensures the reliability of the solder joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [29] reported that the grain size of Cu 6 Sn 5 IMC increased with increasing reflow time, but the addition of TiO 2 suppressed the growth of the IMC due to TiO 2 particles preventing the diffusion between Cu and Sn atoms. It was also reported that the solder properties improved due to the enhancement in the growth of the interfacial IMC layer [20,24,26,30]. Therefore, it can be surmised that the growth of the IMC layers during multiple reflow soldering needs to be controlled or limited as it improves solder properties and ensures the reliability of the solder joints.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, geopolymer ceramics consists of several elements such as Si and Al which may also contribute to the properties of the solder alloy. In our previous research [30,32] the effect of the addition of kaolin geopolymer ceramic (KGC) onto the properties of Sn-3.0Ag-0.5Cu (SAC305) under as-reflowed and isothermal aging conditions was investigated. The results confirmed that the addition of KGC as reinforcement particles in SAC305 enhanced its properties in as-reflowed and isothermal aging conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Even though HASL is the most popular method, it still uses lead in a significantly large portion [9]. To completely remove lead from the surface finish, pure tin plating has become the most popular option due to its good solderability and lower cost [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of Sn-3.0Ag-0.5Cu composite solder with kaolin geopolymer ceramic reinforcement on microstructure and mechanical properties under isothermal ageing, resulting in the morphology of interfacial IMC layer of non-reinforced SAC305 and SAC305-KGC composite solder joints, showed a duplex IMC structure comprises of scallop-type Cu 6 Sn 5 and layer-type Cu 3 Sn [14].…”
mentioning
confidence: 99%